Effectiveness of e-module based on guided discovery learning on learning outcomes of high school students - Alysa Luthfiani; Yerimadesi Yerimadesi (Jurnal Pijar Mipa, 2022)
This study aims to analyze the effectiveness of e-module colligative properties of solutions based on guided discovery learning in improving high school student learning outcomes. The research was conducted on class XII students in a public high school space (MAN 1 Padang) with 36 students. The type of research used is quasi-experimental. The research design was a randomized control-group pretest-posttest design, and data analysis used a t-test. The sample was taken by a simple random sampling technique. The level of effectiveness of the e-module is analyzed from the results of the n-gain value. It obtained an n-gain value of 0.71 in the high category. In conclusion, guided discovery learning based on the chemistry e-module effectively improves student learning outcomes with high criteria. Keywords: Effectiveness, E-Module, Guided Discovery Learning, Learning Outcomes.